Nonparametric estimation of the ruin probability in the classical compound poisson risk model - Yuan Gao; Lingju Chen; Jiancheng Jiang; Honglong You (Journal of Risk and Financial Management, 2020)
In this paper we study estimating ruin probability which is an important problem in insurance. Our work is developed upon the existing nonparametric estimation method for the ruin probability in the classical risk model, which employs the Fourier transform but requires smoothing on the density of the sizes of claims. We propose a nonparametric estimation approach which does not involve smoothing and thus is free of the bandwidth choice. Compared with the Fourier-transformation-based estimators, our estimators have simpler forms and thus are easier to calculate. We establish asymptotic distributions of our estimators, which allows us to consistently estimate the asymptotic variances of our estimators with the plug-in principle and enables interval estimates of the ruin probability.
Keywords: 330; classical risk model; nonparametric estimation; ruin probability